Konsep Pendidikan Sufistik Dalam Bekerja - Abdulloh Arif Mukhlas; Alissa Qothrun Nada (Jurnal Pendidikan Agama Islam Miazhar, 2025)
Rich and poor are already written in destiny. Allah determines a person's sustenance written when they are 4 months old in the womb, to be rich or poor, to be lucky or unfortunate. If sustenance has been determined, then why do we work. So, at first glance, this explanation gives rise to a contradictory understanding when combined with the basic idea that orders us to work, because money does not come by itself, Allah never sends down rain in the form of gold, silver or rupiah. How do Sufis live their spiritual lives, always prioritizing the afterlife, while work is a means of acquiring worldly material goods? But without work, how can they fulfill their worldly needs? This study examines how the concept works in Sufi teachings from the perspective of Imam al-Ghozali, using descriptive qualitative research methods. Data collection in this study is a literature study of the Qur'an, hadith, books, and scientific journals. The results of this study demonstrate that working does not conflict with Sufi teachings. Work has a religious value. Imam Al-Ghazali even stated that working is better than begging. The influence of not working can foster laziness, dependence on others, low self-esteem, ingratitude, and envy. These traits contradict the fundamental teachings of Sufism.